2008
DOI: 10.1111/j.1447-073x.2007.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of palmaris longus agenesis: Common anatomical aberration

Abstract: Palmaris longus muscle, although of little functional use to the human upper limb, assumes great importance when used as a donor tendon for transfer or transplant. The variability in the prevalence of palmaris longus agenesis among various ethnic groups has been established, and the surgeon's awareness of the prevalence in a population or ethnic group is desirable. The prevalence of palmaris longus agenesis has, to the best of the authors' knowledge, not been reported in Indian patients. Five hundred Indian pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
54
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 8 publications
11
54
0
8
Order By: Relevance
“…These findings are in agreement with the work done by many other researchers 6,10,11 . However, there were no differences in the agenesis of the PLMT on either gender.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings are in agreement with the work done by many other researchers 6,10,11 . However, there were no differences in the agenesis of the PLMT on either gender.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study PLMT agenesis was recorded in 17.50% of the population. The incidence rate of agenesis observed in our study is comparable to what was observed in an Indian study and a Nigerian study with recorded rates of 17.2% and 12.6% respectively 5,10 .…”
Section: Discussionsupporting
confidence: 77%
“…The prevalence of agenesis was found to be significantly more common on the left side [3,34]. This corresponds to our study, in which four subjects had a unilateral PLM on the right side while only two subjects showed a unilateral PLM on the left side.…”
Section: Discussionsupporting
confidence: 69%
“…The PLM can be absent unilateral and bilateral in about 22.4% of human beings (Caucasians) with a range of 3.0%-63.9%, depending on the ethnic background of a population [2]. A great diversity is reported between different populations in the prevalence of absence of the PLM [3].…”
Section: Introductionmentioning
confidence: 99%
“…Klasik el cerrahisi kitaplarında m. palmaris longus'un yokluğunun insidansı %15 olarak bildirilmesine rağmen etnik gruplarda yapılan kapsamlı çalışmalarda birbirinden farklı sonuçlara ulaşılmıştır. Kasın bulunmaması durumu %63.9 oranla, en yüksek Türk toplumunda bildirilirken, Hindistan' da yapılan bir çalışmada %17.2, Çin' de yapılan bir çalışmada %4.6, Gana' da yapılan bir çalışmada %3.1 olarak rapor edilmiştir (2, 7,21,22 (10) ise arcus palmaris superficialis'leri varyasyonlu vakaların %33'ün de kasın bulunmadığını belirlemişler, varyasyonlar arasındaki istatistiksel ilişkiyi değerlendir-memişlerdir. Olgumuzda m. palmaris longus yokluğu ile birlikte arcus palmaris superficialis'in oluşmadığı ve elin palmar yüzünde sadece a. ulnaris'in dağıldığı ve baş parmak hariç diğerlerinin bu arter tarafından beslendiği göz-lendi.…”
Section: Discussionunclassified